Peran Karang Taruna Marsada Dalam Pembinaan Remaja Di Desa Hutapaung Kecamatan Pollung Kabupaten Humbang Hasundutan - Irvan Marzuki Lumban Gaol; Bebby Mashito Batubara; Yurial Arief lubis (Universitas Medan Area, 2022)
The problem in this study is that many teenagers in Hutapaung Village are trapped in bad associations ranging from drinking liquor, illegal racing, fights between villages, gambling, wandering to sexual acts outside marriage or free sex. Dragging teenagers into bad associations is relatively easy, where teenagers are very easily influenced by negative things that offer false comfort. This is where the Marsada Youth Organization in Hutapaung Village is expected to have a role in fostering the development of youth creativity. The purpose of this research is to find out how the Marsada Youth Organization plays a role in the development of youth in Hutapaung Village, Pollung District, Humbang Hasundutan Regency and to find out what are the obstacles/inhibitors for the Marsada Youth Organization role. in youth development. This study uses a qualitative descriptive method using the analysis of role theory proposed by J. Dwinarwoko and Bagong Suyanto that the role can guide someone in behavior because the role function is to give direction to the socialization process and can unite groups or communities. The results of this study can be concluded that the role of Karang Taruna Marsada has not been going well because there are still problems or obstacles faced by Karang Taruna Marsada in carrying out its development, such as the lack of participation of members of the Karang Taruna Marsada in participating in activities and the lack of preparation of funds in carrying out activities.